2022
DOI: 10.1080/02635143.2022.2116423
|View full text |Cite
|
Sign up to set email alerts
|

Affordances and obstacles when integrating digital tools into science teaching in preschools

Abstract: Background: Although science and technology are viewed as closely related subjects, they are rarely combined in preschools. Purpose: This article investigates preschool teachers' perspectives on integrating digital tools when teaching science, asking how and why they use digital tools, and examining the affordances they experience and obstacles they encounter when incorporating digital tools. Sample: Eighteen Swedish preschool teachers volunteered to participate in the study. Design and method: Data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
5
0
5
Order By: Relevance
“…The child orientation was visible, for instance, in the themes of accessing children's learning, stimulating engagement and learning and approaching the content. The teacher's considerations consisted of thoughts including digital tools in teaching for documenting children's learning, which is in line with Walan and Enochsson (2022). In this child-oriented learning context, the teachers, based on their knowledge of children's learning needs, saw the children as producers when engaging with digital tools.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The child orientation was visible, for instance, in the themes of accessing children's learning, stimulating engagement and learning and approaching the content. The teacher's considerations consisted of thoughts including digital tools in teaching for documenting children's learning, which is in line with Walan and Enochsson (2022). In this child-oriented learning context, the teachers, based on their knowledge of children's learning needs, saw the children as producers when engaging with digital tools.…”
Section: Discussionmentioning
confidence: 96%
“…According to Fragkiadaki et al (2019), children's perspectives and experiences are essential in conceptualising science. Recent research has shown that digital tools complement other tools of both digital and analogue characters (Walan & Enochsson, 2022). Digital tools can be viewed as a means of teaching to approach scientific content (Johnston, 2019), where technologies next to children's experiences are the critical impetus for children's interest in science content, and digital tools are used for curiosity and reflection (John & Higgins, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flera studier som behandlar digitalisering av undervisning understryker lärarens avgörande betydelse för utbildningens kvalitet i de digitala kontexterna (Bers, 2018a;Fallon, 2013;Marklund, 2020;Neumann & Neumann, 2014;Walan & Enochsson, 2022). Dock har insatser för att stödja lärare att verka i digitaliserade sammanhang i form av adekvat utbildning, tydliga direktiv, tillgång till lämpliga hård-och mjukvaror och teknisk support i hög grad försummats (Kjällander, 2019;Woo & Falloon, 2023).…”
Section: Inledningunclassified